Village Government's Strategy in Implementing the Maternal and Child Health Revolution Policies - Rifatolistia Tampubolon; Arwyn Weynand Nusawakan; Kanako Shinkawa; Gloria Ndoen; Kristiani Desimina Tauho; Treesia Sujana (GLOBAL HEALTH SCIENCE GROUP, 2023)
Maternal health in Timor Tengah Selatan (TTS), East Nusa Tenggara Province, Indonesia, remains an unsolved health problem. It needs women's participation in maternal health care and social role and supports to solve the problem. This research aims to identify the role of village leaders and family decision-making concerning the increased utilization of maternal health services. Objective: This case study was conducted in Binaus Village, Mollo Tengah Sub-district, TTS, East Nusa Tenggara, by six village officials. This is qualitative research that employed a case study. The analysis units in the research were village officials and family heads by employing in-depth interviews and thirty-four family heads by employing Focus Group Discussion (FGD). The data was analyzed by using thematic analysis. There were seven themes revealed, mothers' health is essential for Binaus people, the information source comes from Binaus people themselves, most of the people are obedient to village officials' suggestions and instructions, sanctions granting to improve the use of health facilities and services, the implementation of local government's programs related to mother's and child's health, the existence of transition in decision making, and the preference of health workers use. In the end, the impact of the village leader's support towards maternal health causes a transition in Binaus society in terms of optimizing maternal health services and influencing the decision-making process of families to actively support their maternal mothers actively get better health checkups.